The Effect of Halbach Array Configuration on Permanent-Magnet Synchronous Generator (PMSG) Outer-Runner - Baqaruzi, Syamsyarief; Afit Miranto, Afit; Wahyuda, Dede (Malikussaleh University, Aceh, Indonesia, 2021)
Permanent-Magnet Synchronous Generator it can provide highly reliable power generation with small in size, no copper losses in the rotor circuit, no need for external excitation. We designed and simulated the PMSG with 12 slots and 8 poles with an alternating polarity magnet configuration: NN-SS-NN-SS-NN-SS-NN-SS-NN-SS-NN magnetic flux per pole in the outer stator and the inner stator has been assumed to be constant, following sizes and materials described in this paper. The generator's number of poles is determined by stacking several sections of the magnet side by side and grouping opposite poles in a continuous pattern. the initial design of the PMSG 12 slots and 8 poles outer-runner compare to see how the halbach array configuration changes the output parameter, it will be included. Proportional to the load size and speed The larger the magnetic flux generated by the movement of the magnetic field, the higher the rpm, and the heavier the coil magnetic flux obtained, the higher the induced voltage. This research use five speed variations varying from 1000 to 5000 rpm and load variation from 5 ohm, 15 ohm, 30 ohm, 60 ohm, and 100 ohm. With the effect that the flux distribution is voltage generated at a 5 ohm load only increases at 1000 rpm, while the increase in torque produces an increase in the amount of input power at 30 ohm, which is equal to both the speed and the amount of torque, where the input power increases at all speeds at a load of 30 ohm. This also arises when the output power generated at a load of 30 ohm increases by a high efficiency of over 86%.